Positive electrode and electrochemical device and electronic device using the same
By using a positive electrode active material composed of vulcanized polyacrylonitrile with high sulfur content and low sulfur content in lithium sulfur batteries, the problems of low energy density and poor circulation stability of traditional lithium sulfur batteries are solved, and the effect of significantly improving the energy density and retention rate is achieved.
Patent Information
- Application Number
- CN202180015146.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-10-26
AI Technical Summary
Traditional lithium-sulfur batteries are prone to form polysulfides and "dead sulfur" during charging and discharging, resulting in low energy density and poor circulation stability. It is difficult for existing methods to effectively improve the energy density.
Using a positive electrode active material consisting of high sulfur content vulcanized polyacrylonitrile and low sulfur content vulcanized polyacrylonitrile, a good conductive pathway and capacity are constructed by combining these two materials, thereby improving the energy density and energy density retention rate of the electrochemical device.
It significantly improves the energy density and energy density retention rate of lithium-sulfur batteries, takes into account high sulfur content and good kinetic performance, and improves the cycle stability and rate performance of the battery.
Smart Images

Figure CN115104202B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to a positive electrode and an electrochemical device and an electronic device using the positive electrode. Background Art
[0002] Electrochemical devices (e.g., lithium-sulfur batteries) have high energy density and have become a research and development hotspot for the next generation of high energy density energy storage systems. Traditional lithium-sulfur batteries use elemental sulfur as the positive electrode, which is prone to form shuttle polysulfides and "dead sulfur" during the charge and discharge process, resulting in capacity decay. Lithium-sulfur batteries prepared using sulfurized polyacrylonitrile materials as positive electrodes have a high utilization rate of sulfur positive electrodes, and no polysulfides are formed when matched with ester electrolytes. They are more stable during the cycle process, and therefore have attracted much attention. However, the commonly used sulfurized polyacrylonitrile materials have a low sulfur content, resulting in a low energy density of lithium-sulfur batteries. Increasing their sulfur content will seriously affect the kinetic properties of the material, and still cannot effectively improve the energy density of lithium-sulfur batteries.
[0003] In view of the above, there is a need to provide an improved positive electrode to improve the energy density and energy density retention of electrochemical devices. Summary of the invention
[0004] The present application attempts to solve at least one problem existing in the related art to at least some extent by providing a positive electrode and an electrochemical device and an electronic device using the same.
[0005] According to one aspect of the present application, the present application provides a positive electrode, which includes a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material is a sulfurized polyacrylonitrile having a sulfur content of 45wt% to 60wt%, and the second positive electrode active material is a sulfurized polyacrylonitrile having a sulfur content of 30wt% to 40wt%.
[0006] According to an embodiment of the present application, a ratio of the sulfur content in the first positive electrode active material to the sulfur content in the second positive electrode active material is 1.1 to 1.5.
[0007] According to an embodiment of the present application, based on the weight of the positive electrode, the ratio of the mass of the sulfur element in the first positive electrode active material to the mass of the sulfur element in the second positive electrode active material is 1 to 3.
[0008] According to an embodiment of the present application, the particle size of the first positive electrode active material is 2 μm to 5 μm, and the particle size of the second positive electrode active material is 0.5 μm to 3 μm.
[0009] According to an embodiment of the present application, the ratio of the particle size of the first positive electrode active material to the particle size of the second positive electrode active material is 2.5 to 5.
[0010] According to an embodiment of the present application, the first positive electrode active material and the second positive electrode active material form an agglomerate, and according to an elemental analysis test method, the second positive electrode active material contacts and surrounds the surface of the first positive electrode active material.
[0011] According to the embodiment of the present application, the compaction density of the positive electrode is 1.2 g / cm 3 Up to 1.5g / cm 3 .
[0012] According to another aspect of the present application, the present application provides an electrochemical device, which includes a negative electrode, an electrolyte and a positive electrode according to the present application.
[0013] According to an embodiment of the present application, the electrolyte contains a phosphoester additive, and the content of the phosphoester additive is 2% to 4% based on the weight of the electrolyte.
[0014] According to an embodiment of the present application, the phosphite additive includes at least one of trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, diethyl phenyl phosphite or tris(trimethylsilyl) phosphite.
[0015] According to an embodiment of the present application, the negative electrode includes at least one of lithium metal, lithium-copper composite strip, lithium alloy, lithium-supplemented graphite material or lithium-supplemented silicon material.
[0016] According to yet another aspect of the present application, the present application provides an electronic device, which includes the electrochemical device according to the present application.
[0017] By using the positive electrode provided in the present application, the energy density and energy density retention rate of the electrochemical device can be significantly improved.
[0018] Additional aspects and advantages of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The following will briefly describe the drawings necessary for describing the embodiments of the present application or the prior art to facilitate the description of the embodiments of the present application. Obviously, the drawings described below are only some of the embodiments in the present application. For those skilled in the art, without the need for creative work, drawings of other embodiments can still be obtained based on the structures illustrated in these drawings.
[0020] Figure 1 A schematic diagram showing the elemental analysis test method.
[0021] Figure 2 The energy density curves of the lithium-sulfur batteries of the comparative examples and embodiments of the present application as a function of the number of cycles are shown. DETAILED DESCRIPTION
[0022] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0023] In the detailed description and claims, a list of items connected by the term "at least one of" may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements. The term "at least one of" has the same meaning as "at least one of."
[0024] positive electrode
[0025] Traditional lithium-sulfur batteries use a system of elemental sulfur matching ether electrolytes. During the charge and discharge process, they will present a solid-liquid-solid reaction path, and the generated polysulfide has a serious shuttle effect, which will cause the battery capacity to decay and then fail. Sulfurized polyacrylonitrile materials have a special structure (that is, sulfur exists in the form of small molecules S2-S6 and is confined in the carbon skeleton) so that they can present a solid-solid reaction path when matched with carbonate electrolytes, thereby avoiding the shuttle effect caused by polysulfides. Lithium-sulfur batteries prepared with sulfurized polyacrylonitrile materials have low self-discharge and more stable cycles, so they have attracted much attention.
[0026] However, the sulfurized polyacrylonitrile material is obtained by heat treatment of sulfur and polyacrylonitrile, and usually has a low sulfur content. Therefore, the energy density of lithium-sulfur batteries prepared from this low-sulfur sulfurized polyacrylonitrile material is relatively low. Researchers usually use the following methods to improve the energy density of lithium-sulfur batteries, but these methods still have many problems:
[0027] (1) The sulfur content in the polyacrylonitrile sulfide material can be increased by improving the process. However, after the sulfur content is increased, the kinetic properties of the polyacrylonitrile sulfide material will deteriorate. The lithium-sulfur battery assembled in this way suffers from severe cycle attenuation, poor high-rate performance, and low capacity utilization. The overall energy density of the battery has not been effectively improved.
[0028] (2) Polyacrylonitrile sulfide can be used for doping (for example, selenium-doped polyacrylonitrile sulfide), but this method has limited improvements in energy density and rate performance and is relatively costly.
[0029] (3) A new type of aqueous conductive binder can be used to improve the rate performance to a certain extent, but this method is costly and the commonly used conductive agents of this type will lead to an increase in the amount of electrolyte used, which is not conducive to improving the overall energy density of the battery.
[0030] (4) Additives such as redox mediator additives and capacity extenders can be introduced into the electrolyte. Although this method can improve the rate performance and energy density, the cost of the additives involved is usually very high, and such additives often cause deterioration of the negative electrode side, resulting in poor battery cycle performance.
[0031] The present application solves the above problems by combining the use of high-sulfur content sulfurized polyacrylonitrile and low-sulfur content sulfurized polyacrylonitrile as positive electrode active materials, significantly improving the energy density and energy density retention rate of electrochemical devices (e.g., lithium-sulfur batteries). Specifically, the present application provides a positive electrode, which comprises a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material is a sulfurized polyacrylonitrile having a sulfur content of 45wt% to 60wt%, and the second positive electrode active material is a sulfurized polyacrylonitrile having a sulfur content of 30wt% to 40wt%. The sulfurized polyacrylonitrile with a low sulfur content has good conductivity, and when used in combination with the sulfurized polyacrylonitrile with a high sulfur content, a good conductive path can be constructed. At the same time, the sulfurized polyacrylonitrile with a low sulfur content is an active material, which can provide capacity for the battery. After the sulfurized polyacrylonitrile with a low sulfur content is used in combination with the sulfurized polyacrylonitrile with a high sulfur content, the high sulfur content and good kinetics of the composite positive electrode can be taken into account, thereby achieving the effect of improving energy density and energy density retention rate.
[0032] In some embodiments, the first positive electrode active material is a sulfurized polyacrylonitrile having a sulfur content of 45 wt%, 50 wt%, 55 wt% or 60 wt%. In some embodiments, the second positive electrode active material is a sulfurized polyacrylonitrile having a sulfur content of 30 wt%, 33 wt%, 35 wt%, 38 wt% or 40 wt%.
[0033] The thermal stability of high-sulfur polyacrylonitrile (with a sulfur content of 45wt% to 60wt%) can reach more than 350 degrees, and the thermal stability of low-sulfur polyacrylonitrile (with a sulfur content of 30wt% to 40wt%) can reach more than 500 degrees. Cutting the positive electrode by focused ion beam (FIB) will not destroy the shape and structure of the active material particles therein, and then testing the sulfur content of the particles in the cross section after cutting by elemental analysis method can obtain the sulfur content of high-sulfur polyacrylonitrile and low-sulfur polyacrylonitrile. This test method can eliminate the influence of binders and conductive agents in the positive electrode.
[0034] In some embodiments, the ratio of the sulfur content in the first positive electrode active material to the sulfur content in the second positive electrode active material is 1.1 to 1.5. In some embodiments, the ratio of the sulfur content in the first positive electrode active material to the sulfur content in the second positive electrode active material is 1.1, 1.2, 1.3, 1.4, 1.5 or in the range of any of the above values. When the ratio of the sulfur content in the first positive electrode active material to the sulfur content in the second positive electrode active material is within the above range, it helps to further improve the energy density and energy density retention of the electrochemical device.
[0035] In some embodiments, based on the weight of the positive electrode, the ratio of the mass of sulfur in the first positive electrode active material to the mass of sulfur in the second positive electrode active material is 1 to 3. In some embodiments, based on the weight of the positive electrode, the ratio of the mass of sulfur in the first positive electrode active material to the mass of sulfur in the second positive electrode active material is 1, 1.5, 2, 2.5, 3, or within the range formed by any of the above values. When the ratio of the mass of sulfur in the first positive electrode active material to the mass of sulfur in the second positive electrode active material is within the above range, it helps to further improve the energy density and energy density retention of the electrochemical device.
[0036] In some embodiments, the particle size of the first positive electrode active material is 2μm to 5μm, and the particle size of the second positive electrode active material is 0.5μm to 3μm. In some embodiments, the particle size of the first positive electrode active material is 2μm, 3μm, 4μm, 5μm, or within the range of any of the above values. In some embodiments, the particle size of the second positive electrode active material is 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, or within the range of any of the above values. When the particle sizes of the first positive electrode active material and the second positive electrode active material are within the above range, it helps to further improve the energy density and energy density retention of the electrochemical device.
[0037] In some embodiments, the ratio of the particle size of the first positive electrode active material to the particle size of the second positive electrode active material is 2.5 to 5. In some embodiments, the ratio of the particle size of the first positive electrode active material to the particle size of the second positive electrode active material is 2.5, 3, 3.5, 4, 4.5, 5, or within the range of any of the above values. When the ratio of the particle size of the first positive electrode active material to the particle size of the second positive electrode active material is within the above range, it helps to further improve the energy density and energy density retention of the electrochemical device.
[0038] In some embodiments, the first positive electrode active material and the second positive electrode active material form agglomerates, and according to an elemental analysis test method, the second positive electrode active material contacts and surrounds the surface of the first positive electrode active material.
[0039] In some embodiments, the compaction density of the positive electrode is 1.2 g / cm 3 Up to 1.5g / cm 3 In some embodiments, the compaction density of the positive electrode is 1.2 g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 Or within the range formed by any of the above values. When the compaction density of the positive electrode is within the above range, it helps to further improve the energy density and energy density retention rate of the electrochemical device.
[0040] In some embodiments, the positive electrode active material layer further includes a binder. The binder can improve the bonding between the positive electrode active material particles and can improve the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, the binder includes, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin and nylon, etc.
[0041] In some embodiments, the positive electrode active material layer also includes a conductive material to impart conductivity to the electrode. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0042] In some embodiments, the positive electrode current collector includes, but is not limited to, aluminum (Al).
[0043] Electrolyte
[0044] In some embodiments, the electrolyte contains a phosphorus ester additive. The combination of the positive electrode active material of the present application and the electrolyte containing the phosphorus ester additive helps to further improve the energy density and energy density retention rate of the electrochemical device.
[0045] In some embodiments, the phosphite additive includes at least one of trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, diethyl phenyl phosphite or tris(trimethylsilyl) phosphite.
[0046] In some embodiments, the content of the phosphoester additive is 2% to 4% based on the weight of the electrolyte. In some embodiments, the content of the phosphoester additive is 2%, 2.5%, 3%, 3.5%, 4% or within the range of any of the above values based on the weight of the electrolyte.
[0047] The lithium salts that can be used in the electrolyte of the embodiment of the present application include, but are not limited to: inorganic lithium salts, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiSbF6, LiSO3F, LiN(FSO2)2, etc.; fluorine-containing organic lithium salts, such as LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonyl imide lithium, cyclic 1,2-tetrafluoroethane disulfonyl imide lithium, LiN(CF3SO2)(C4F9S O2), LiC(CF3SO2)3, LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium salts containing dicarboxylic acid complexes, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, lithium tetrafluoro(oxalato)phosphate, etc. In addition, the above lithium salts can be used alone or in combination of two or more. In some embodiments, the lithium salt includes a combination of LiPF6 and LiBF4. In some embodiments, the lithium salt includes an inorganic lithium salt such as LiPF6 or LiBF4 and a fluorine-containing organic lithium salt such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2. In some embodiments, the concentration of the lithium salt is in the range of 0.8mol / L to 3mol / L, in the range of 0.8mol / L to 2.5mol / L, in the range of 0.8mol / L to 2mol / L, or in the range of 1mol / L to 2mol / L. In some embodiments, the concentration of the lithium salt is about 1mol / L, about 1.15mol / L, about 1.2mol / L, about 1.5mol / L, about 2mol / L, or about 2.5mol / L.
[0048] The solvents that can be used in the electrolyte of the embodiments of the present application include, but are not limited to: cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, cyclic ethers, chain ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.
[0049] In some embodiments, the cyclic carbonate includes, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate. In some embodiments, the cyclic carbonate has 3-6 carbon atoms.
[0050] In some embodiments, the linear carbonates include, but are not limited to: dimethyl carbonate (DMC), ethyl methyl carbonate, diethyl carbonate, methyl n-propyl carbonate, ethyl n-propyl carbonate, di-n-propyl carbonate and the like; as fluorine-substituted linear carbonates, for example, bis(fluoromethyl) carbonate, bis(difluoromethyl) carbonate, bis(trifluoromethyl) carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate and 2,2,2-trifluoroethyl methyl carbonate.
[0051] In some embodiments, the cyclic carboxylic acid ester includes, but is not limited to, γ-butyrolactone and γ-valerolactone. In some embodiments, part of the hydrogen atoms of the cyclic carboxylic acid ester may be substituted with fluorine.
[0052] In some embodiments, the chain carboxylic acid ester includes, but is not limited to: methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate and ethyl pivalate. In some embodiments, part of the hydrogen atoms of the chain carboxylic acid ester can be substituted by fluorine. In some embodiments, the fluorine-substituted chain carboxylic acid ester includes, but is not limited to: methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate and 2,2,2-trifluoroethyl trifluoroacetate.
[0053] In some embodiments, cyclic ethers include, but are not limited to, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl 1,3-dioxolane, 4-methyl 1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, and dimethoxypropane.
[0054] In some embodiments, the chain ethers include, but are not limited to, dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane, and 1,2-ethoxymethoxyethane.
[0055] In some embodiments, the sulfur-containing organic solvent includes, but is not limited to: sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, methyl propyl sulfone, dimethyl sulfoxide, methyl methanesulfonate, ethyl methanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, diethyl sulfate and dibutyl sulfate. In some embodiments, some hydrogen atoms of the sulfur-containing organic solvent may be substituted by fluorine.
[0056] In some embodiments, the aromatic fluorine-containing solvent includes, but is not limited to, fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and trifluoromethylbenzene.
[0057] In some embodiments, the solvent used in the electrolyte of the present application includes one or more of the above. In some embodiments, the solvent used in the electrolyte of the present application includes cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes an organic solvent selected from a group consisting of the following substances: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, ethyl acetate, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, or a combination thereof.
[0058] The additives that can be used in the electrolyte of the embodiment of the present application include, but are not limited to: compounds having 2-3 cyano groups and compounds containing sulfur-oxygen double bonds.
[0059] In some embodiments, the compound having 2-3 cyano groups may include at least one selected from succinonitrile (SN), adiponitrile (ADN), ethylene glycol bis(propionitrile) ether (EDN), 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile (HTCN), 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane (TCEP) or 1,2,4-tris(2-cyanoethoxy)butane.
[0060] In some embodiments, the compound containing sulfur-oxygen double bonds includes, but is not limited to, at least one of vinyl sulfate and 1,2-propylene glycol sulfate.
[0061] The electrolyte of the present application can be prepared by any known method. In some embodiments, the electrolyte of the present application can be prepared by mixing the components.
[0062] negative electrode
[0063] The negative electrode includes a negative electrode current collector and a negative electrode active material disposed on one or both surfaces of the negative electrode current collector. The specific types of the negative electrode active material are not subject to specific restrictions and can be selected according to needs.
[0064] In some embodiments, the negative electrode includes at least one of lithium metal, lithium copper composite tape, lithium alloy, lithium-supplemented graphite material, or lithium-supplemented silicon material.
[0065] In some embodiments, the negative electrode active material includes a binder. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. Non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, etc.
[0066] In some embodiments, the negative electrode active material includes a conductive material to impart conductivity to the electrode. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanotubes, etc.), metal-based materials (e.g., metal powders, metal fibers, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.
[0067] Isolation film
[0068] In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0069] In some embodiments, the isolation film includes a substrate layer. In some embodiments, the substrate layer is a non-woven fabric, a film or a composite film having a porous structure. In some embodiments, the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. In some embodiments, the material of the substrate layer is selected from polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film.
[0070] In some embodiments, a surface treatment layer is provided on at least one surface of the substrate layer. In some embodiments, the surface treatment layer can be a polymer layer, an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. In some embodiments, the polymer layer comprises a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).
[0071] In some embodiments, the inorganic layer includes inorganic particles and a binder. In some embodiments, the inorganic particles are selected from one or more combinations of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. In some embodiments, the binder is selected from one or more combinations of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0072] Electrochemical Devices
[0073] The present application also provides an electronic device, which includes a positive electrode, a negative electrode and an electrolyte according to the present application.
[0074] The electrochemical device of the present application includes any device in which an electrochemical reaction occurs, and its specific examples include all kinds of primary batteries, secondary batteries or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery. In some embodiments, the electrochemical device of the present application includes a positive electrode sheet having a positive active material capable of absorbing and releasing metal ions; a negative electrode sheet according to an embodiment of the present application; an electrolyte; and a separator disposed between the positive electrode sheet and the negative electrode sheet.
[0075] Electronic Devices
[0076] The present application further provides an electronic device, which includes the electrochemical device according to the present application.
[0077] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0078] The preparation of lithium-ion batteries is described below by taking lithium-ion batteries as an example and combining specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.
[0079] Example
[0080] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.
[0081] 1. Preparation of lithium-ion batteries
[0082] 1. Preparation of positive electrode
[0083] Example 1
[0084] According to the mass ratio of 8.36:9.64:1:0.5:0.5, sulfurized polyacrylonitrile with a sulfur content of 45% (average particle size of 5μm), sulfurized polyacrylonitrile with a sulfur content of 39% (average particle size of 3μm), conductive agent Super P, sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) were weighed, and an appropriate amount of deionized water was added to mix into a uniform slurry with a solid content of 20%. The slurry was evenly coated on an aluminum foil with a carbon bottom coating using a coating machine and vacuum dried at 90°C for 18 hours. The dried pole piece was not cold-pressed, but was directly cut into a disc with a diameter of 1.4cm using a punching machine to obtain a positive electrode.
[0085] Example 2
[0086] The positive electrode was prepared by a method substantially the same as that in Example 1, except that the obtained electrode was subjected to 3-ton cold pressing before being cut into pieces.
[0087] Example 3
[0088] The positive electrode was prepared by a method substantially the same as that in Example 2, except that the raw materials were sulfurized polyacrylonitrile with a sulfur content of 52%, sulfurized polyacrylonitrile with a sulfur content of 35%, SuperP, CMC and SBR in a mass ratio of 7.24:10.76:1:0.5:0.5.
[0089] Example 4
[0090] The positive electrode was prepared by a method substantially the same as that in Example 2, except that the raw materials were sulfurized polyacrylonitrile with a sulfur content of 52%, sulfurized polyacrylonitrile with a sulfur content of 39%, Super P, CMC and SBR in a mass ratio of 7.7:10.3:1:0.5:0.5.
[0091] Example 5
[0092] The positive electrode was prepared by a method substantially the same as that in Example 2, except that the raw materials were sulfurized polyacrylonitrile with a sulfur content of 59%, sulfurized polyacrylonitrile with a sulfur content of 30%, Super P, CMC and SBR in a mass ratio of 8.6:9.4:1:0.5:0.5.
[0093] Example 6
[0094] The positive electrode was prepared by a method substantially the same as that in Example 2, except that the raw materials were sulfurized polyacrylonitrile with a sulfur content of 52%, sulfurized polyacrylonitrile with a sulfur content of 39%, Super P, CMC and SBR in a mass ratio of 13.5:4.5:1:0.5:0.5.
[0095] Example 7
[0096] The positive electrode was prepared by a method substantially the same as that in Example 2, except that the raw materials were sulfurized polyacrylonitrile with a sulfur content of 52%, sulfurized polyacrylonitrile with a sulfur content of 39%, Super P, CMC and SBR in a mass ratio of 12:6:1:0.5:0.5.
[0097] Example 8
[0098] The positive electrode was prepared by a method substantially the same as that in Example 2, except that the raw materials were sulfurized polyacrylonitrile with a sulfur content of 52%, sulfurized polyacrylonitrile with a sulfur content of 39%, Super P, CMC and SBR in a mass ratio of 9:9:1:0.5:0.5.
[0099] Example 9
[0100] The positive electrode was prepared by a method substantially the same as that in Example 2, except that the raw materials were sulfurized polyacrylonitrile with a sulfur content of 52%, sulfurized polyacrylonitrile with a sulfur content of 39%, Super P, CMC and SBR in a mass ratio of 6:12:1:0.5:0.5.
[0101] Example 10
[0102] The positive electrode was prepared by a method substantially the same as that of Example 7, except that the particle size of the sulfurized polyacrylonitrile with a sulfur content of 52% was 2 μm, and the particle size of the sulfurized polyacrylonitrile with a sulfur content of 39% was 1 μm.
[0103] Embodiment 11
[0104] The positive electrode was prepared by a method substantially the same as that of Example 7, except that the particle size of the sulfurized polyacrylonitrile having a sulfur content of 39% was 1.8 μm.
[0105] Example 12
[0106] The positive electrode was prepared by a method substantially the same as that of Example 7, except that the particle size of the sulfurized polyacrylonitrile having a sulfur content of 39% was 1 μm.
[0107] Embodiment 13
[0108] The positive electrode was prepared by a method substantially the same as that of Example 7, except that the particle size of the sulfurized polyacrylonitrile having a sulfur content of 39% was 0.5 μm.
[0109] Embodiment 14
[0110] The positive electrode was prepared by the same method as in Example 11, except that the positive electrode slurry was prepared by the following method: sulfurized polyacrylonitrile with a sulfur content of 52% and sulfurized polyacrylonitrile with a sulfur content of 39% were mixed in a mass ratio of 12:6, and then liquid phase surface treatment was performed, dried at 90°C, and then heat treated at 240°C for 3 hours to obtain a powder. The obtained powder was mixed with Super P, CMC and SBR in a mass ratio of 18:1:0.5:0.5, and deionized water was added to mix into a uniform slurry.
[0111] Embodiment 15
[0112] The positive electrode was prepared by a method substantially the same as that in Example 14, the only difference being that the obtained electrode was subjected to 7-ton cold pressing before being cut into pieces.
[0113] Example 16
[0114] The positive electrode was prepared by a method substantially the same as that in Example 14, the only difference being that the obtained electrode was subjected to 12-ton cold pressing before being cut into pieces.
[0115] Embodiment 17
[0116] The positive electrode was prepared by a method substantially the same as that of Example 15, except that 2 wt % of tris(trimethylsilyl) phosphite was added to the electrolyte.
[0117] Embodiment 18
[0118] The positive electrode was prepared by a method substantially the same as that of Example 15, except that 4 wt % of tris(trimethylsilyl) phosphite was added to the electrolyte.
[0119] Embodiment 19
[0120] The positive electrode was prepared by a method substantially the same as that of Example 15, except that 6 wt % of tris(trimethylsilyl) phosphite was added to the electrolyte.
[0121] Embodiment 20
[0122] The positive electrode was prepared by a method substantially the same as that in Example 15, except that 3 wt % of diethyl phenyl phosphite was added to the electrolyte.
[0123] Embodiment 21
[0124] The positive electrode was prepared by a method substantially the same as that in Example 15, except that 1.5 wt % of trimethyl phosphite was added to the electrolyte.
[0125] Comparative Example 1
[0126] The positive electrode was prepared by a method substantially the same as that in Example 1, except that the raw materials were sulfurized polyacrylonitrile (average particle size of 5 μm) with a sulfur content of 45%, Super P, CMC and SBR in a mass ratio of 18:1:0.5:0.5.
[0127] Comparative Example 2
[0128] The positive electrode was prepared by a method substantially the same as that in Example 1, except that the raw materials were sulfurized polyacrylonitrile (average particle size of 5 μm) with a sulfur content of 52%, Super P, CMC and SBR in a mass ratio of 18:1:0.5:0.5.
[0129] Comparative Example 3
[0130] The positive electrode was prepared by a method substantially the same as that in Example 1, except that the raw materials were sulfurized polyacrylonitrile (average particle size of 5 μm) with a sulfur content of 59%, Super P, CMC and SBR in a mass ratio of 18:1:0.5:0.5.
[0131] Comparative Example 4
[0132] The positive electrode was prepared by a method substantially the same as that in Example 1, except that the raw materials were sulfurized polyacrylonitrile (average particle size of 3 μm) with a sulfur content of 39%, Super P, CMC and SBR in a mass ratio of 18:1:0.5:0.5.
[0133] Comparative Example 5
[0134] The positive electrode was prepared by a method basically the same as in Example 1, except that the raw materials were sulfurized polyacrylonitrile with a sulfur content of 40% (average particle size of 5 μm), sulfurized polyacrylonitrile with a sulfur content of 25% (average particle size of 3 μm), Super P, CMC and SBR in a mass ratio of 6.92:11.08:1:0.5:0.5.
[0135] 2. Preparation of negative electrode
[0136] A circular lithium sheet with a diameter of 1.6 cm and a thickness of 300 μm was used as the negative electrode.
[0137] 3. Preparation of electrolyte
[0138] Ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed evenly in a mass ratio of 1:1, and then LiPF6 (1 mol / L) was added and stirred evenly to obtain a basic electrolyte. According to the setting of the embodiment, the target compound was added to the basic electrolyte to obtain an electrolyte.
[0139] 4. Preparation of isolation membrane
[0140] A circular polyethylene (PE) porous polymer film with a diameter of 1.9 cm was used as a separator.
[0141] 5. Preparation of batteries
[0142] The positive electrode, the separator and the negative electrode are stacked in order, placed in a button-type battery packaging shell, and the electrolyte is injected and packaged to obtain a battery.
[0143] 2. Test Method
[0144] 1. Test method for sulfur content in positive electrode active materials
[0145] A cross section of the positive electrode removed from the battery was cut out using FIB, and the particles with a size greater than 500nm on the diagonal line from the upper left corner to the lower right corner of the screen were tested in point mode by X-ray energy spectrum analysis (EDS) to analyze the mass fraction of sulfur in the particles. This method can remove the influence of the conductive agent and binder on the surface of the sulfide polyacrylonitrile particles on the elemental analysis. The number of tested particles was adjusted to at least 10 by adjusting the test magnification. The mass fraction of the sulfur content of each particle was then analyzed. After eliminating the data with a sulfur content of less than 5%, the maximum value was recorded as Max and the minimum value was recorded as Min.
[0146] When (Max-Min) / Min≤5%, it is considered that the first positive electrode active material and the second positive electrode active material have the same sulfur content. When (Max-Min) / Min>5%, it is considered that the first positive electrode active material and the second positive electrode active material have different sulfur contents, and the values greater than (Max+Min) / 2 are averaged and recorded as the sulfur content of the first positive electrode active material, and the values less than (Max+Min) / 2 are averaged and recorded as the sulfur content of the second positive electrode active material.
[0147] 2. Test method for mass ratio of sulfur element
[0148] Use FIB to cut a cross section of the positive electrode removed from the battery, and select at least 3 areas on the cross section for EDS testing, and the magnification is set to 5000 times. The test method is the same as "1. Test method for sulfur content in positive electrode active materials". The sulfur content of the first positive electrode active material is recorded as A, and the sulfur content of the second positive electrode active material is recorded as B. The ratio of the area of the first positive electrode active material to the area of the second positive electrode active material in the test area is statistically recorded as C. Since the density of sulfurized polyacrylonitrile with different sulfur contents is not much different, the area ratio C can be considered as the mass fraction ratio of the first positive electrode active material to the second positive electrode active material in the area. The mass fraction ratio D of the sulfur element between the first positive electrode active material and the second positive electrode active material in each test area is calculated by the following formula:
[0149]
[0150] The D values obtained from three randomly acquired different regions are averaged to obtain the mass fraction ratio of the sulfur element of the first positive electrode active material to the second positive electrode active material in the positive electrode.
[0151] 3. Test method for particle size of positive electrode active materials
[0152] Use ion polishing or FIB to cut a cross section of the positive electrode removed from the battery, and analyze it through a scanning electron microscope (SEM) with a magnification of 3000-5000 times. According to the method described in "1. Test method for sulfur content in positive electrode active materials", determine the high sulfur content and low sulfur content sulfurized polyacrylonitrile particles, and test the particle size of the corresponding sulfurized polyacrylonitrile particles, and take the average value. The particle size uses the equivalent circle diameter.
[0153] 4. Method for determining whether the first positive electrode active material and the second positive electrode active material form agglomerates
[0154] Cut a cross section of the cycled positive electrode using CP or FIB, and analyze it using a scanning electron microscope (SEM) with a magnification of 5000-8000 times. Determine the location of high-sulfur and low-sulfur sulfurized polyacrylonitrile particles according to the method described in "1. Test method for sulfur content in positive electrode active materials". Figure 1 As shown, the black particles represent the sulfurized polyacrylonitrile particles with a high sulfur content, the gray particles represent the sulfurized polyacrylonitrile particles with a low sulfur content, and the dotted line part represents the binder and the conductive agent, etc. When the particles in the picture meet the following two conditions, it is considered that the first positive electrode active material and the second positive electrode active material form agglomerates:
[0155] (1) The high-sulfur content sulfurized polyacrylonitrile particles are in contact with and surrounded by at least two low-sulfur content sulfurized polyacrylonitrile particles; and
[0156] (2) There are at least three sulfide polyacrylonitrile particles in the image that satisfy condition (1).
[0157] 5. Test methods for energy density and energy density retention of lithium-sulfur batteries
[0158] The button cell was tested using the Blue Electric test system. The battery was discharged at 0.05C in the first cycle, charged and discharged at 0.1C (i.e., small rate activation) in the 2nd to 4th cycles, and then charged and discharged at 0.4C in the 5th to 30th cycles. The energy density of the battery was tested after each cycle, and a curve of energy density versus cycle number was drawn. The mass of the positive electrode is the sum of the mass of the first positive electrode active material, the second positive electrode active material, the binder, and the conductive agent.
[0159] The ratio of the energy density after the 30th cycle to the energy density after the 5th cycle was recorded as the energy density retention rate.
[0160] 3. Test Results
[0161] Table 1 shows the effects of the positive electrode and the electrolyte on the energy density and energy density retention rate of the lithium-sulfur battery in the examples and comparative examples of the present application.
[0162] As shown in Comparative Examples 1-3, when the sulfurized polyacrylonitrile with a higher sulfur content (≥45wt%) is used as the only positive electrode active material, the energy density and energy density retention rate of the lithium-sulfur battery are low and cannot meet the use requirements. As shown in Comparative Example 4, when the sulfurized polyacrylonitrile with a lower sulfur content (≤40wt%) is used as the only positive electrode active material, although the lithium-sulfur battery has a higher energy density retention rate, its absolute energy density is low and cannot meet the use requirements. Although Comparative Example 5 uses two sulfurized polyacrylonitrile with different sulfur contents as positive electrode active materials, the sulfur content of these two sulfurized polyacrylonitrile is low. Although it can improve the energy density retention rate of the lithium-sulfur battery, its absolute energy density is too low and cannot meet the use requirements.
[0163] As shown in Examples 1-21, when the positive electrode active material includes both sulfurized polyacrylonitrile with a high sulfur content (45wt%-60wt%) and sulfurized polyacrylonitrile with a low sulfur content (30wt% to 40wt%), the lithium-sulfur battery has both a high absolute energy density and a high energy density retention rate.
[0164] As shown in Examples 1-5, when the ratio of the sulfur content in the first positive electrode active material to the sulfur content in the second positive electrode active material is in the range of 1.1 to 1.5, the energy density and energy density retention rate of the lithium-sulfur battery can be improved simultaneously.
[0165] As shown in Examples 4 and 6-9, when the ratio of the mass of sulfur element in the first positive electrode active material to the mass of sulfur element in the second positive electrode active material is in the range of 1 to 3, the positive electrode has a better energy density retention rate (greater than 97%) while maintaining a high energy density (the energy density at the 5th cycle is greater than 665Wh / Kg and the energy density at the 30th cycle is greater than 650Wh / Kg).
[0166] As shown in Examples 7 and 10-13, when the particle size of the first positive electrode active material is 2 μm to 5 μm and the particle size of the second positive electrode active material is 0.5 μm to 3 μm, the positive electrode has high energy density and energy density retention. When the ratio of the particle size of the first positive electrode active material to the particle size of the second positive electrode active material is in the range of 2.5 to 5, it helps to further improve the energy density and energy density retention of the lithium-sulfur battery.
[0167] As shown in Examples 11 and 14, when the first positive electrode active material and the second positive electrode active material form agglomerates so that the second positive electrode active material surrounds the surface of the first positive electrode active material, the energy density and energy density retention rate of the lithium-sulfur battery can be further improved.
[0168] As shown in Examples 14-16, when the compaction density of the positive electrode is 1.2 g / cm 3 Up to 1.5g / cm3 When the energy density is within the range of , the positive electrode has better energy density and energy density retention rate.
[0169] As shown in Examples 15 and 17-21, on the basis of using sulfurized polyacrylonitrile with a high sulfur content (45wt%-60wt%) and sulfurized polyacrylonitrile with a low sulfur content (30wt% to 40wt%) as the positive electrode active material, the use of an electrolyte containing 2wt% to 4wt% of a phosphite additive can further significantly improve the energy density of the lithium-sulfur battery while maintaining a high energy density retention rate.
[0170] also, Figure 2 The energy density curves of the lithium-sulfur batteries of Comparative Example 2, Comparative Example 4, Example 11, Example 15 and Example 17 of the present application with the number of cycles are shown. The results show that when the positive electrode active material includes both sulfurized polyacrylonitrile with a high sulfur content (45wt%-60wt%) and sulfurized polyacrylonitrile with a low sulfur content (30wt% to 40wt%), the energy density of the lithium-sulfur battery is significantly improved. When the first positive electrode active material and the second positive electrode active material form agglomerates so that the second positive electrode active material surrounds the surface of the first positive electrode active material, the energy density of the lithium-sulfur battery can be further improved. The use of an electrolyte containing a phosphorus ester additive helps to further improve the energy density of the lithium-sulfur battery.
[0171]
[0172]
[0173] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.
[0174] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A positive electrode comprising a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material is a sulfurized polyacrylonitrile having a sulfur content of 45 wt % to 60 wt %, and the second positive electrode active material is a sulfurized polyacrylonitrile having a sulfur content of 30 wt % to 40 wt %. 2 . The positive electrode according to claim 1 , wherein a ratio of a sulfur content in the first positive electrode active material to a sulfur content in the second positive electrode active material is 1.1 to 1.
5. 3 . The positive electrode according to claim 1 , wherein a ratio of a mass of sulfur element in the first positive electrode active material to a mass of sulfur element in the second positive electrode active material is 1 to 3 based on a weight of the positive electrode. 4 . The positive electrode according to claim 1 , wherein a particle size of the first positive electrode active material is 2 μm to 5 μm, and a particle size of the second positive electrode active material is 0.5 μm to 3 μm. 5 . The positive electrode according to claim 4 , wherein a ratio of a particle size of the first positive electrode active material to a particle size of the second positive electrode active material is 2.5 to 5. 6 . The positive electrode according to claim 1 , wherein the first positive electrode active material and the second positive electrode active material form an agglomerate, and according to an elemental analysis test method, the second positive electrode active material contacts and surrounds the surface of the first positive electrode active material.
7. The positive electrode according to claim 1, wherein the compaction density of the positive electrode is 1.2 g / cm 3 Up to 1.5g / cm 3 .
8. An electrochemical device comprising a negative electrode, an electrolyte and a positive electrode according to any one of claims 1 to 7. 9 . The electrochemical device according to claim 8 , wherein the electrolyte comprises a phosphorus ester additive, and the content of the phosphorus ester additive is 2% to 4% based on the weight of the electrolyte.
10. The electrochemical device according to claim 9, wherein the phosphite additive comprises at least one of trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, diethyl phenyl phosphite or tris(trimethylsilyl) phosphite.
11. The electrochemical device according to claim 8, wherein the negative electrode comprises at least one of lithium metal, lithium copper composite tape, lithium alloy, lithium-supplemented graphite material or lithium-supplemented silicon material.
12. An electronic device comprising the electrochemical device according to any one of claims 8 to 11.
Citation Information
Patent Citations
Sulphidepolymer coated sulfur / carbon composite material and preparation method thereof
CN104241612A
Lithium ion battery electrode active material and preparation method thereof
CN104577050A